Nanoemulsion of Nagasari (Mesua ferrea L.) Leaf and Its Activity Against Staphylococus aureus - Suhesti, Tuti Sri; Muslimah, Annisa (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Nagasari leaves (Mesua ferrea L.) contain special chemicals to fight S. aureus. Nanoparticle technology can improve the solubility, stability, and bioavailability of the phytochemicals found in herbal medicines. The nanoemulsion produces small particle sizes. It has a large surface area. This research aims to determine the physical stability of Nagasari leaf ethanol extract nanoemulsion (EDN) with variations of Virgin Coconut Oil (VCO) as the oil phase during storage and its activity. Nanoemulsions were produced using 1%, 2%, and 3% VCO concentrations. The physical properties and stability of the preparations were characterised. The nanoemulsion was tested for activity against S. aureus. Chloramphenicol was used as a positive control. The results showed that the nanoemulsion containing 1% VCO produced the best physical properties: a particle size of 23.137 ± 7.63 nm, a polydispersity index (PDI) of 0.203 ± 0.013, and a zeta potential of -18.9 ± 0.086. A VCO concentration of 1% produces good nanoemulsion stability. The F1 nanoemulsion exhibited an average inhibition zone diameter of 16.75 mm (strong), the EDN provided an inhibition zone diameter of 8.70 mm (medium), and the positive control exhibited an inhibition zone diameter of 24.30 mm (very strong).